One-pot Synthesis of 2-Hydroxy-1,4-Naphthoquinone (Lawsone) - Sivakumar, Dhanavel; Thanusu, Jayaraman; Kanagarajan, Vijayakumar; Nagarajan, Samuthira; Manikandan, Haridoss; Gopalakrishnan, Mannathusamy (Current Organic Synthesis, 2019)
Aims and Scope: The 2-hydroxy-1,4-naphthoquinone (lawsone) and 2,5-dihydroxy-1, 4-naphthoquninone (5-hydroxylawsone) are synthesized by one step process. The process involves an inexpensive catalyst urea hydrogen peroxide and a base (t-BuOK) in alcohol for the transformation of 1-naphthol or 2,5-dihydroxynaphthalene to lawsone or its derivatives in the presences of oxygen. The process is further directed to produce lawsone or its derivatives, with no extraneous heating to make it energetically efficient. The synthesized compounds are analyzed by FT-IR, 1H and 13C NMR spectral studies. Materials and Methods: All the raw materials were purchased from commercial suppliers and used as such without further purification. The infrared spectra were recorded on a Thermo Nicolet-Avatar-330 FT-IR spectrophotometer using KBr (pellets) and noteworthy absorption values (cm-1) are obtained. 1H and 13C NMR spectra are recorded at 293K on BRUKER AMX-400 Spectrometer operating with the frequencies of 300 MHz and 75, 125 MHz respectively using DMSO-d6 as solvent. Results: The 2-hydroxy-1,4-naphthoquinone (lawsone) and 2,5-dihydroxy-1,4-naphthoquninone (5- hydroxylawsone) are synthesised from 1-naphthol and 1,5-dihydorxynaphalene with urea-hydrogen peroxide as the catalyst in basic medium and oxygen as the oxidizing agent. After purification, the formed products are analysed by IR and NMR spectroscopy. The yield is 82% and the purity of the products is > 95%. Conclusion: The present study highlights the process for the manufacturing of lawsone and its derivatives which is efficient in terms of energy needed for the activation of products from reactants. The advantages include its cost-effective nature in terms of simple inexpensive catalyst required for the process and high yield. The mild reaction conditions employed and the harmless by product obtained further confirm the usefulness of this synthetic process.
Keywords: cost-effective